Neurotisisme Memprediksi Peningkatan Organizational Citizenship Behavior Pada Konteks Organisasi Non-profit: Studi Pada Pengurus Organisasi Orkestra di Indonesia - Gracia, Josephine; Himawan, Karel Karsten (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2022)
Literature has demonstrated the important role of personality as predictor of organizational citizenship behavior (OCB) in an organization. However, little is known regarding to what extent that personality predicts OCB in orchestra organizations, especially in Indonesia, where orchestra organizations are emerging in the recent years. Such a gap calls for study to ensure effective and efficient organizational management. The current study aims at exploring the role of personality in predicting OCB of Indonesian orchestra organizations. A sample of 84 orchestra committee members participated in the study. Results demonstrated that neuroticism was the only significant predictor of OCB among Indonesian orchestra group members. The findings present valuable information for orchestra management in mapping their organizational strategies for effective management.